Heparin-Modified Amniotic Membrane Combined With Growth Factors for Promoting Corneal Wound Healing After Alkali Burn - Zhao, Xuan; Zuo, Xin; Zhong, Jing; Wang, Bowen; Li, Saiqun; Xiao, Yichen; Yuan, Jin (Frontiers in Bioengineering and Biotechnology, 2020)
Ocular chemical burns are potentially blinding ocular injuries and require urgent management. Amniotic membrane (AM) transplantation is an effective surgical treatment, one of the reasons is because AM is a rich source of growth factors that can promote epithelialization and wound healing. However, growth factors will be gradually lost and insufficient after preparation process and long-time storage, leading to unsatisfactory therapeutic effects. Herein, we present a modified amniotic membrane (AM-HEP) for the supplement and sustained release of growth factor by surface grafting heparin for treatment of ocular chemical burns. Heparin grafting rate and stability, microstructure, physical property, sustained release of epithelial growth factor (EGF) of AM-HEP were characterized. Biocompatibility and ability to promote corneal epithelial cells growth and migration were evaluated in vitro. The therapeutic effects of AM-HEP combined with EGF (AM-HEP@EGF) in vivo had been evaluated in model of mouse corneal alkali burn. The results indicated that heparin was introduced into AM and maintain stability over 3 weeks at 37 oC. The modification process of AM-HEP did not affect microstructure and physical property after comparing with non-modified AM. EGF could be combined quickly and effectively with AM-HEP, the sustained release could last for more than 14 days. AM-HEP@EGF could significantly promote corneal epithelial cells growth and migration, compared with non-modified AM and control group. Faster corneal epithelialization was observed with the transplantation of AM-HEP@EGF in vivo, compared with the untreated control group. The corneas in AM-HEP@EGF group have less inflammation and was more transparent than those in control group. The results from in vitro and in vivo experiments demonstrated that AM-HEP@EGF could significantly enhance the therapeutic effects. Taken together, AM-HEP@EGF is exhibited to be a potent clinical application in corneal alkali burns through accelerating corneal epithelial wound healing.